Preliminary study to consider the preparation of a business strategy for The Regional Public Service Agency (BLUD) in the water tourism area of Gita Nada and Gili Sulat Lawang Lombok, NTB Province - Hidayati, Baiq Yuliani; Lahindah, Laura (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to obtain fundamental information that will be used as a reference in formulating business strategies for Regional Business Services Agencies (BLUD) in the Gita Nada and Gili Sulat Lawang marine tourism areas in NTB Province. This conservation area has huge tourism potential with an estimated economic value of tourism resources based on Willingness To Pay (WTP) reaches more than 17 billion rupiah per year. However, the use of this tourist destination is still not optimal. This study uses a survey method through interviews with the management, local communities, and related company partners. The survey results show that BLUD business development in this region faces several challenges, among which the most impactful are budget problems and limited human resources. Based on these findings, this study proposes an effective business strategy to optimize the potential of the tourist area. The proposed strategy is expected to increase the income and welfare of tourism industry players in the region, as well as make a positive contribution to the local economy. With the implementation of this strategy, it is hoped that this aquatic tourism area can develop sustainably and provide maximum benefits for all parties involved.